2017
DOI: 10.1002/ecs2.1705
|View full text |Cite
|
Sign up to set email alerts
|

Selecting habitat to what purpose? The advantage of exploring the habitat–fitness relationship

Abstract: Abstract. Measures of reproductive success have been recognized in many fields as essential tools to assess the status of populations, species, and communities. However, difficulties in gathering data on reproductive success often prevent researchers from taking advantage of the information offered by those measures. For example, most of habitat selection studies do not include reproductive success in their analysis even though doing so would highly improve our understanding of the habitat selection process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
(151 reference statements)
1
12
0
Order By: Relevance
“…As expected, leopards were more likely to prey on cattle and wolves tended to prey more on sheep/goat which confirms the differences in the predation strategies of these carnivores: open areas are generally more suitable for wolves which are cursorial predators (Uboni, Smith, Stahler, & Vucetich, ), preferring open areas to hunt and killing shoat in open pastures (Behdarvand et al., ; Treves et al., ). Leopards preyed substantially more on cattle perhaps because cattle were more likely to graze in forest habitat, which is suitable for ambush hunting by leopards.…”
Section: Discussionsupporting
confidence: 63%
“…As expected, leopards were more likely to prey on cattle and wolves tended to prey more on sheep/goat which confirms the differences in the predation strategies of these carnivores: open areas are generally more suitable for wolves which are cursorial predators (Uboni, Smith, Stahler, & Vucetich, ), preferring open areas to hunt and killing shoat in open pastures (Behdarvand et al., ; Treves et al., ). Leopards preyed substantially more on cattle perhaps because cattle were more likely to graze in forest habitat, which is suitable for ambush hunting by leopards.…”
Section: Discussionsupporting
confidence: 63%
“…Support for adaptive habitat selection beyond the nest scale is rare (Chalfoun & Martin, 2007;Uboni, Smith, Stahler, & Vucetich, 2017; but see Joos et al, 2014;Kosterman, Squires, Holbrook, Pletsher, & Hebblewhite, 2018), with typical explanations including alternative fitness components not measured (i.e., Desare et al, 2014) or anthropogenic disturbance altering traditional fitness cues (i.e., DeCesare, 2012;Weldon and Haddad, 2005). Yet, we found that flycatcher selection for reduced forest cover within 1,200 m showed a clear nest survival benefit.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating both chick survival and adult survival simultaneously into our analyses, we attempted to eliminate any unobserved components of such a risk-to-reproduction tradeoff associated with these species. Such unobserved components have been posited as a potential source of ambiguity associated with studies assessing how adaptive habitat selection influences reproductive success and overall fitness (Bloom et al, 2013;Uboni et al, 2017 2002) or if a species is more likely to allocate resources for selfmaintenance. For instance, it has been suggested that scaled quail have adapted to arid and semi-arid regions (such as our study area) by allocating more resources toward self-maintenance rather than toward reproductive output whereas the opposite is true for bobwhite because they evolved under more mesic conditions (Giuliano, Patiño, & Lutz, 1998 (Bacon et al, 2016;Ficetola, Miaud, Pompanon, & Taberlet, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, though many studies illustrate fitness consequences for adults associated with adaptive behavior during the brooding life-history stage (Blomberg et al, 2013;Hagen, Pitman, Sandercock, Robel, & Applegate, 2011;Mangelinckx, Davis, Allen, Sullivan, & Blomberg, 2018;Zhao et al, 2018), rarely have studies linked adaptive brooding behaviors to offspring survival while simultaneously assessing fitness consequences of the attending adults. By decoupling these two demographic consequences, equivocal results may arise when attempting to link adaptive habitat selection to either offspring survival or attending adult survival separately because this pattern in space use may be more beneficial toward an unobserved demographic parameter rather than the observed parameter (Uboni, Smith, Stahler, & Vucetich, 2017). Thus, attempting to understand concurrent demographic trade-offs between offspring survival and adult survival associated with brood habitat selection is important when assessing the conservation implications of these behavioral modifications.…”
Section: Introductionmentioning
confidence: 99%